The factors that affect fruit and vegetable consumption behavior in adolescents at Junior High School 10 Tangerang South City - Nuraisha Sanuri Milenia; Debby Endayani Safitri; Imawati Eka Putri (Arsip Keilmuan Gizi (AKG), 2024)
Consumption of fruit and vegetables in Indonesia is still very low, especially among teenagers. This can cause various kinds of health problems. This study aimed to determine what factors can affect fruit and vegetable consumption behavior in adolescents at Junior High School 10 Tangerang South City. Fruit and vegetable consumption behavior was measured using the SQ-FFQ. This study used a quantitative method with a cross-sectional study design and used accidental sampling technique with 116 respondents as a subject. Statistical analysis used in this study is the Independent T-test and Spearman Rank Correlation test. The results of the study showed that the average fruit and vegetable consumption of students in Junior High School 10 Tangerang South City was 283.98 grams/day. Bivariate results showed that there was a significant difference in the average consumption behavior of fruit and vegetables with gender (p=0.028), fruit and vegetable preference (p=0.029), fruit and vegetable availability (p=0.026), exposure to mass media (p=0.000) and intention to consume fruit and vegetables (p=0.000), but there was no significant difference in the average behavior of fruit and vegetable consumption with self-image perception (p=0.945) and nutritional knowledge (p=0.379).